2013
DOI: 10.1021/jf403789r
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Specific Consumption of Galactooligosaccharides by Bifidobacterial Species

Abstract: Prebiotics are non-digestible substrates that stimulate the growth of beneficial microbes in the human intestine. Galactooligosaccharides (GOS) are food ingredients that possess prebiotic properties, in particular, promoting the growth of bifidobacteria in situ. However precise mechanistic details of GOS consumption by bifidobacteria remains poorly understood. Because GOS are mixtures of polymers of different lengths and linkages, there is interest to determine which specific structures provide prebiotic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…Previous studies on GOS consumption by Bifidobacterium strains showed that each strain consumed GOS at different rates and growth rate was directly attributed to the ability of the Bifidobacterium species to use specific isomers within the GOS mixtures40. Our study shows that B. thetaiotaomicron uses almost all isomers in the GOS mixture.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies on GOS consumption by Bifidobacterium strains showed that each strain consumed GOS at different rates and growth rate was directly attributed to the ability of the Bifidobacterium species to use specific isomers within the GOS mixtures40. Our study shows that B. thetaiotaomicron uses almost all isomers in the GOS mixture.…”
Section: Discussionsupporting
confidence: 50%
“…maturation of the immune system, pathogen exclusion, and regulation of mood and behaviour (Nicholson et al ., ). The preferential metabolism of short β‐galactosides of different origin by bifidobacteria is well established (Davis et al ., ; Peacock et al ., ). By contrast, the molecular recognition and specificity determinants of β‐galactosidases in Bifidobacterium and other gut microbiota members, remain elusive.…”
Section: Discussionmentioning
confidence: 97%
“…lactis shows a different isomer‐specific utilization pattern of commercial β‐galacto‐oligosaccharides as compared to B. longum subsp. infantis and B. adolescentis (Peacock et al ., ), which are persistent members of human infant and adult gut microbiota respectively. Thus, B. animalis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly administered prebiotics include lactulose, inulin, polydextrose, short-chain (sc) and long-chain (lc) fructo-oligosaccharides and galacto-oligosaccharides, and combinations of the above. The potential complexity of the prebiotic approach to altering the gut microbiota is exemplified by the observations that different isomers of GOS are preferentially consumed by different species of Bifidobacterium 112 and that some gut pathogens (e.g. E coli EHEC and C. perfringens ) are able to consume some isomers of GOS 113 .…”
Section: Introductionmentioning
confidence: 99%